الاغتراب النفسي وعلاقته بمستوى الطموح لدى طلبة السنة أولى جامعي في ضوء بعض المتغيرات - أولاد هدار، زينب (جامعة عمار ثليجي بالأغواط, 2016)
The present study aimed to identify the existing relationship between phenomenon of the psychological alienation and the level of aspiration among a sample of Ghardaïa in the first year university students, it also seeks to detect the differences in degrees of the psychological alienation according to the following variables: the sex of the student, his academic specialty. The study resulted to negative correlation between phenomenon of the psychological alienation and the level of aspiration among the study sample, and showed the existing of significant differences in the degrees of students psychological alienation according to the variable of sex for the benefit of females, while the absence of statistically significant differences in the psychological alienation according to the variable of academic Specialization
تهدف الدراسة الحالية إلى التعرف عن العلاقة القائمة بين ظاهرة الاغتراب النفسي ومستوى الطموح لدى عينة من طلبة السنة أولى جامعي بجامعة غرداية، كما تسعى إلى الكشف عن الفروق في درجات الاغتراب النفسي تبعاً للمتغيرات التالية: جنس الطالب والتخصص الأكاديمي. وقد توصلت الدراسة إلى وجود علاقة ارتباطية سالبة بين ظاهرة الاغتراب النفسي ومستوى الطموح لدى عينة الدراسة، كما بينت النتائج إلى وجود فروق جوهرية في درجات الطلاب في الاغتراب النفسي تعزي لمتغير الجنس لصالح الإناث، بينما لا توجد فروق دالة إحصائياً في درجات الاغتراب النفسي تعزي لمتغير التخصص الأكاديمي.
Keywords: الاغتراب النفسي -- طلاب الجامعات -- علم النفس الاجتماعي